IMPLEMENTASI NILAI-NILAI PENDIDIKAN KARAKTER DI SD TA'MIRUL ISLAM SURAKARTA - Rhohana, Siti (ISTORIA : Jurnal Pendidikan dan Ilmu Sejarah, 2023)
Abstract: Currently, Indonesia is in a state of moral degradation, this can be seen from the many events that do not reflect good character, for example, do not behave honestly, prioritize their own interests, always depend on others, etc. This example is a simple thing, but if it continues, it will have a negative impact. So character building is a must for students because education not only makes students smart, but also has character. The easiest character building can be done when children are still in elementary school. That is why the cultivation of character education at the elementary level is very necessary. This study aims to examine the implementation of character education in Ta'mirul Islam Elementary School Surakarta. The method used by the researcher is descriptive qualitative. The data collection technique used was through observation and interviews with principals, teachers and guardians of students. Based on the research results obtained, the implementation of character education in SD Ta'mirul Islam is carried out through integration in learning, extracurricular activities, and habituation. Integration is carried out on all subjects and integration directly through Islamic religious learning and Civics. Values that can be integrated are religious, honest, disciplined, love for the homeland, hard work, etc. Extracurricular activities are also a means to create character in students. Extracurricular activities carried out at Ta'mirul Islam Elementary School include scouts, little preachers, tambourines, recitations, Al Qur'an, Scouts, Arabic, Calligraphy, and tahfidz Al Qur'an.Keywords: Implementation, Character Education, Elementary School